EVALUATION AND OPTIMIZATION OF NEW GAS WELL DEVELOPMENT TO ENHANCE PRODUCTION PERFORMANCE IN THE ANGGANA FIELD, PERTAMINA HULU INDONESIA ZONE 9, EAST KALIMANTAN - Rahmady Rusdiantje; Boni Swadesi; Nur Suhascaryo (Institut Teknologi Sepuluh Nopember, 2025)
The Anggana Field, located in Kutai Kartanegara Regency, East Kalimantan, is part of Pertamina Hulu Indonesia (PHI) Zone 9, which manages several mature oil and gas fields in the Mahakam region. The discovery of new gas reserves in Anggana presents an opportunity to enhance production, but the existing surface facilities were primarily designed for oil handling and are limited in gas capacity. This study focuses on the technical optimization of gas transportation from Anggana by using PIPESIM software to simulate network performance and flow assurance under different pipeline configurations. Simulation scenarios were designed to evaluate two configurations: (1) a tie-in to the existing Sanga-Sanga gas network and (2) a dedicated pipeline from Anggana to the Lempake Booster Station. The simulation assesses pressure drop, temperature profile, and flow stability across both systems. Results show that the tie-in configuration increases upstream backpressure and reduces throughput, while the dedicated pipeline provides stable pressure distribution and maintains flow assurance without exceeding design limits. This technical analysis demonstrates that PIPESIM is a reliable tool for evaluating production network performance and supports decision-making in brownfield gas developments.